2001
DOI: 10.1021/jo010216z
|View full text |Cite
|
Sign up to set email alerts
|

Direct Synthesis of Previously Inaccessible Bridgehead Azabicyclics by Intramolecular Cyclization of α-Sulfonamido and α-Sulfonimido Radicals

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 78 publications
0
18
0
Order By: Relevance
“…Despite these structural differences, all bridged sultams 392 were found to be hydrolytically stable. Using radical cyclization reaction, Paquette also reported the synthesis of bridged disulfonimide with a [3.2.2] ring system (Scheme 105), 438 and complex tricyclic bridged sultams. 439 The X-ray structure of 394 438 showed a large θ value ( 394 : θ = 345.8°; 392c : θ = 325.2°), indicating a relatively flexible sulfonimide bond in this compound.…”
Section: Synthesis Of Bridged Lactams With Complex Ring Systems Anmentioning
confidence: 99%
“…Despite these structural differences, all bridged sultams 392 were found to be hydrolytically stable. Using radical cyclization reaction, Paquette also reported the synthesis of bridged disulfonimide with a [3.2.2] ring system (Scheme 105), 438 and complex tricyclic bridged sultams. 439 The X-ray structure of 394 438 showed a large θ value ( 394 : θ = 345.8°; 392c : θ = 325.2°), indicating a relatively flexible sulfonimide bond in this compound.…”
Section: Synthesis Of Bridged Lactams With Complex Ring Systems Anmentioning
confidence: 99%
“…In fact, lithiation of 3 with t BuLi was described by Paquette and co‐workers; the carbanion formed was used in the reaction with reactive alkylation reagents (i.e. allyl and benzyl bromides) . We have found that reaction of 3a–d with n BuLi in THF at –78 °C, followed by trapping of the organolithium species with carbon dioxide and acidic work‐up gave the target carboxylic acids 10a–d in 55–72 % yield.…”
Section: Resultsmentioning
confidence: 91%
“…Synthesis of the compound was previously reported by Paquette and colleagues by an alternative method …”
Section: Resultsmentioning
confidence: 99%
“…The importance of the sulfonamide function in the construction of the third and final ring of the molecule becomes fully apparent at this juncture. Deprotonation of 10 with t BuLi11 and capture of the anion with racemic octene oxide activated by BF 3 ⋅OEt 2 12 resulted in the formation of 11 , which was then subjected to a Dess–Martin oxidation13 to give 12 . A one‐pot sequence, which involved sequential β‐elimination and Miyaura borylation14 of the isolable intermediate 13 , resulted in the extremely rapid (20 min; the reaction normally requires >15 h) and highly diastereoselective15 formation of the boronic ester 14 (Scheme ).…”
Section: Methodsmentioning
confidence: 99%